Material for hydrophilic modification of polytetrafluoroethylene microporous membrane and preparation method of material
By introducing benzene ring and long carbon chain hydrophobic chain segments on the PVA skeleton of the polytetrafluoroethylene microporous membrane, and cross-linking of epoxy-based materials and ultraviolet light, the problems of low material modulus and poor water resistance are solved, and the problem of low material modulus and poor water resistance is achieved. Higher resistance to water flattening and stability.
Patent Information
- Application Number
- CN202411149727.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-21
- Publication Date
- 2024-12-27
AI Technical Summary
The polytetrafluoroethylene microporous membrane is prone to deformation due to its low expansion structure modulus, and the existing hydrophilic modification methods lead to poor water resistance of the material and is prone to swelling and dissolving in water.
By introducing benzene ring and long carbon chain hydrophobic chain segments on the PVA skeleton, the material modulus and crosslinking degree are improved, and the polar group content is reduced. Aminobenzaldehyde and PVA condensation reaction and alkylsulfonyl chloride Hinsberg reaction are used to bind the ring The oxygen-based material and ultraviolet light induce cross-linking to form a stable hydrophilic modified film.
The modulus and water-flattening resistance of the PTFE microporous membrane are improved, the polar group content is reduced, the water resistance and stability of the material are enhanced, and the swelling and dissolution phenomenon is avoided.
Smart Images

Figure BDA0005003303210000091 
Figure BDA0005003303210000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polytetrafluoroethylene materials, and in particular relates to a hydrophilic modification technology of a polytetrafluoroethylene microporous membrane. Background Art
[0002] Polytetrafluoroethylene (PTFE) has excellent resistance to strong acids and alkalis, and will not decompose even under high temperature conditions, so it has excellent stability. The microporous membrane made of PTFE can intercept tiny particles due to its special asymmetric polymer chain structure, and has a very high filtration effect due to its chemical corrosion resistance. The filter membrane can meet the filtration of corrosive liquids.
[0003] However, the material itself is chemically inert and has low surface energy, is extremely hydrophobic, and is difficult for water to penetrate. Therefore, it cannot be used directly for liquid water separation and requires hydrophilic modification.
[0004] There are many hydrophilic modification methods disclosed in the prior art. For example, the applicant's prior application, Chinese patent with publication number CN115245743A, discloses a polytetrafluoroethylene microporous membrane and its hydrophilic modification method. DMF solution, triethylamine and PU are added to a reaction container, and the PU solution is prepared by sufficient stirring. The PTFE membrane anchored with perfluoroalkylsulfonyl fluoride is transferred to the PU solution, and the solution is placed under vacuum at -0.06 to -0.1 MPa for 5 to 30 minutes and then allowed to stand for 2 to 10 hours. The PTFE microporous membrane is taken out and placed in an oven at 50 to 80°C for drying for 1 to 4 hours. In this process, the sulfonyl fluoride reacts with the primary and secondary amines of the PU to generate a topological structure, which is anchored on the polytetrafluoroethylene to introduce hydrophilic sulfonamide groups, ether bonds and amino structures. Since the fluorocarbon chain of the Rf-structure has a low surface energy and has good bonding with PTFE, sulfonyl fluoride reacts with the primary and secondary amino groups on the polyether urea structural material to undergo a sulfonylation reaction, and sulfonamide groups, ether bonds and amino structures are introduced into PTFE to enhance the acid and alkali tolerance of the hydrophilic coating.
[0005] Another example is the Chinese patent application with publication number CN117771960 A, which discloses a method for hydrophilic modification of polytetrafluoroethylene membranes. The main steps of the hydrophilic modification method are: soaking the polytetrafluoroethylene membrane in an organic solvent until it is transparent, taking it out and soaking it in a hydrophilic PVA mixed solution, wherein the hydrophilic PVA mixed solution includes PVA and a hydrophilic component containing amino groups; placing the soaked polytetrafluoroethylene membrane in a crosslinking agent aqueous solution, heating the reaction and drying it to obtain a pre-modified polytetrafluoroethylene membrane; placing the pre-modified polytetrafluoroethylene membrane in a γ-glycidyloxypropyltrimethoxysilane aqueous solution, heating the reaction and drying it to obtain a hydrophilic modified polytetrafluoroethylene membrane. It constructs a micro-nano structure on the polytetrafluoroethylene membrane to enhance the hydrophilicity and durability of the modified polytetrafluoroethylene membrane.
[0006] However, since the PTFE microporous membrane is expanded, the modulus is low and it is easy to deform, and the prior art does not solve this problem well. In addition, since the PVA side chain contains a large number of polar hydroxyl groups, it has strong hydrophilicity, resulting in poor water resistance and easy swelling and dissolution in water. Summary of the invention
[0007] In view of the problems existing in the prior art, the present invention provides a material for hydrophilic modification of polytetrafluoroethylene microporous membrane and a preparation method thereof. The hydrophilic modification material is used for hydrophilic modification to solve the problems of easy deformation of PTFE microporous membrane and poor water resistance due to excessively enhanced hydrophilicity.
[0008] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0009] First, a material for hydrophilic modification of polytetrafluoroethylene microporous membrane is provided, including PVA solution, aminobenzaldehyde, glacial acetic acid, alkylsulfonyl chloride, and epoxy material, wherein the glacial acetic acid causes the aldehyde group in the aminobenzaldehyde to react with the hydroxyl group of PVA to undergo acetal reaction and introduce amino groups, and the alkylsulfonyl chloride is used to introduce hydrophobic segments into the PVA.
[0010] Preferably, the PVA solution is prepared by stirring and dissolving polyvinyl alcohol and deionized water in a heated water bath.
[0011] Preferably, the concentration of the PVA solution is 5%; and / or the temperature of the heating water bath is 95°C.
[0012] Preferably, the aminobenzaldehyde is one or more of p-aminobenzaldehyde, o-phenylaminobenzaldehyde, m-phenylaminobenzaldehyde, p-acetylaminobenzaldehyde, 2,4-diaminobenzaldehyde and 2-amino-3,5-dibromobenzaldehyde.
[0013] Preferably, the amount of aminobenzaldehyde added is 5-15% by mass of the PVA solution; and / or the amount of glacial acetic acid added is 1-5% by mass of the PVA solution.
[0014] Preferably, the alkylsulfonyl chloride is one or more of pentanesulfonyl chloride, octanesulfonyl chloride, undecanesulfonyl chloride, dodecanesulfonyl chloride, pentadecanesulfonyl chloride, heptadecanylsulfonyl chloride and octadecanesulfonyl chloride.
[0015] Preferably, the mass percentage of the added alkylsulfonyl chloride in the PVA solution is 2-15%.
[0016] Preferably, the epoxy material is one or more of 4-vinylbenzyl glycidyl ether, allyl glycidyl ether, and glycidyl methacrylate.
[0017] In addition, a method for preparing a hydrophilic modified material is also provided, characterized in that the method for preparing the material comprises the following steps:
[0018] Adding aminobenzaldehyde to the PVA solution;
[0019] Add glacial acetic acid and stir to allow the aldehyde group in aminobenzaldehyde to react with the hydroxyl group of PVA to form an acetal and introduce an amino group;
[0020] After the acetalization reaction is completed, alkylsulfonyl chloride is added and stirred to introduce hydrophobic segments into PVA to obtain a PVA-AbA solution;
[0021] The PVA-AbA solution is transferred to a light-proof reaction container, and an alcohol solvent is first added to prepare a 1-5% solution, and triethylamine is added at a mass percentage of 0.5-3% of the solution for catalysis. Then, the epoxy material is added and stirred after heating to a set temperature and stirring for a set time to react to obtain the product PVA-AbA-Alsc material.
[0022] Preferably, after catalysis, the mixture is heated to 100° C. and stirred for 4-6 hours; and / or, after the epoxy material is added, the stirring time is 10-12 hours.
[0023] The technical solution adopted by the present invention has the following beneficial effects:
[0024] Since the PTFE microporous membrane is expanded, it has a low modulus and is easily deformed, especially when treating high-concentration polluted wastewater, the material itself needs to have a high ability to resist water flattening. In response to this demand, the present invention adopts a technical solution of introducing a benzene ring, which is a rigid group. The introduction of the benzene ring improves the modulus of the PTFE microporous membrane material.
[0025] In order to introduce the benzene ring, a condensation reaction occurred between the aldehyde group of aminobenzaldehyde and the hydroxyl group of PVA to introduce the benzene ring and the amino group into the PVA skeleton.
[0026] Since PVA side chains contain a large number of polar hydroxyl groups and have strong hydrophilicity, they have poor water resistance and are prone to swelling and dissolution in water. Therefore, in addition to increasing the degree of cross-linking, it is also necessary to introduce hydrophobic segments into the cross-linked PVA skeleton macromolecules to reduce the content of polar groups, that is, to reduce the polarity of the polymer so that water cannot enter, or enters less. In response to this demand, the present invention adopts a technical solution of introducing long carbon chain hydrophobic segments.
[0027] The free amino group and alkylsulfonyl chloride undergo Hinsberg reaction to introduce long carbon chain hydrophobic segments on PVA. The introduction of long carbon chain hydrophobic segments further reduces the polarity of PVA, making it easier for PVA to bind to the PTFE surface.
[0028] The specific technical solutions and beneficial effects of the present invention will be described in detail in the following specific embodiments. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Those skilled in the art will appreciate that, in the absence of conflict, the features in the following embodiments and implementations may be combined with each other.
[0031] The embodiment of the present invention first provides a material for hydrophilic modification of polytetrafluoroethylene microporous membrane, including PVA solution, aminobenzaldehyde, glacial acetic acid, alkylsulfonyl chloride, and epoxy material.
[0032] Among them, glacial acetic acid causes the aldehyde group in aminobenzaldehyde to react with the hydroxyl group of PVA to undergo acetal reaction and introduce amino groups and benzene rings. Alkyl sulfonyl chloride is used to introduce hydrophobic segments into PVA. The epoxy group in the epoxy material undergoes a ring-opening reaction with the hydroxyl group of PVA to introduce photosensitive groups into PVA.
[0033] It is to be understood that glacial acetic acid may also be replaced by materials that can perform similar functions.
[0034] The preparation method of the above hydrophilic modified material comprises the following steps:
[0035] Adding aminobenzaldehyde to the PVA solution;
[0036] Add glacial acetic acid and stir to make the aldehyde group in aminobenzaldehyde react with the hydroxyl group of PVA to introduce amino group and benzene ring;
[0037] After the acetalization reaction is completed, alkylsulfonyl chloride is added and stirred to introduce hydrophobic segments into PVA to obtain a PVA-AbA solution;
[0038] The PVA-AbA solution is transferred to a light-proof reaction container, and epoxy material is added to allow the epoxy group to undergo a ring-opening reaction with the hydroxyl group of PVA, thereby introducing a photosensitive group onto the PVA.
[0039] The PVA solution is prepared by stirring and dissolving polyvinyl alcohol and deionized water in a heated water bath. The concentration of the PVA solution is 3-8%, preferably 5%, and the temperature of the heated water bath is 95°C.
[0040] Preferably, the aminobenzaldehyde is p-aminobenzaldehyde, o-phenylaminobenzaldehyde, m-phenylaminobenzaldehyde, p-acetylaminobenzaldehyde, 2,4-diaminobenzaldehyde and 2-amino-3,5-dibromobenzaldehyde, or one or more thereof. Moreover, the amount of aminobenzaldehyde added is 5-15% by mass of the PVA solution, such as 8%, 10%, or 12%; the amount of glacial acetic acid added is 1-5% by mass of the PVA solution, such as 2%, 3%, or 4%.
[0041] Preferably, the alkyl sulfonyl chloride is one or more of pentanesulfonyl chloride, octanesulfonyl chloride, undecanesulfonyl chloride, dodecanesulfonyl chloride, pentadecanesulfonyl chloride, heptadecanylsulfonyl chloride and octadecanesulfonyl chloride. After the acetalization reaction is completed, the alkyl sulfonyl chloride is added, and the mass percentage of the added alkyl sulfonyl chloride to the PVA solution is 2-15%, for example, 3%, 6%, 8%, 10%, 12%.
[0042] Preferably, the epoxy material is one or more of 4-vinylbenzyl glycidyl ether, allyl glycidyl ether, and glycidyl methacrylate.
[0043] In the preparation method of the above-mentioned hydrophilic modified material, the PVA-AbA solution is transferred to a light-proof reaction container, and an alcohol solvent is first added to prepare a 1-5% solution, wherein the alcohol solvent can be one or at least two of methanol, ethanol, propanol, and butanol, and at the same time, 0.5-3% of triethylamine by mass of the solution is added for catalysis, and after heating to a set temperature and stirring for a set time, 1-5% of the epoxy material by mass of the solution is added and stirred for reaction.
[0044] Preferably, after catalysis, the mixture is heated to 100° C. and stirred for 4-6 hours; after the epoxy material is added, the stirring time is 10-12 hours.
[0045] In addition, the embodiment of the present invention also provides a method for hydrophilic modification of a polytetrafluoroethylene microporous membrane, comprising the following steps:
[0046] An alcohol solvent, a hydrophilic modified material and a cationic photoinitiator are added to a light-proof reaction container to prepare a hydrophilic modified photosensitive solution; wherein the mass ratio of the alcohol solvent: the hydrophilic modified material: the cationic photoinitiator is 100:1-3:0.5-1, for example 100:2:0.8.
[0047] Placing the PTFE microporous membrane in the hydrophilic modified photosensitive solution in the reaction container so that the PTFE microporous membrane is evenly coated with a layer of material containing polar groups;
[0048] The PTFE microporous membrane coated with the polar group-containing material is taken out from the reaction container, and is subjected to ultraviolet crosslinking under ultraviolet light irradiation to obtain a hydrophilic polytetrafluoroethylene microporous membrane.
[0049] Wherein, the alcohol solvent is one or at least two of methanol, ethanol, propanol and butanol.
[0050] The PTFE microporous membrane is placed in the hydrophilic modified photosensitive solution in the reaction container, and after degassing for 30-60 minutes with the help of ultrasound and vacuum auxiliary system, it is allowed to stand for 1-6 hours, so that a layer of material containing polar groups is evenly coated on the PTFE.
[0051] On the basis of the above, an embodiment of the present invention further provides a polytetrafluoroethylene microporous membrane, which is modified by the above hydrophilic modification method.
[0052] It can be understood that the polytetrafluoroethylene microporous membrane prepared by the above method can replace the conventional polytetrafluoroethylene microporous membrane and be used in various water treatment devices that originally used conventional polytetrafluoroethylene microporous membranes.
[0053] Since the PTFE microporous membrane is expanded, it has a low modulus and is easily deformed, especially when treating high-concentration polluted wastewater, the material itself needs to have a high ability to resist water flattening. The technical solution specifically adopted in this embodiment is to introduce a benzene ring, which is a rigid group. The introduction of the benzene ring increases the modulus of the PTFE microporous membrane material.
[0054] In order to introduce the benzene ring, a condensation reaction occurred between the aldehyde group of aminobenzaldehyde and the hydroxyl group of PVA to introduce the benzene ring and the amino group into the PVA skeleton.
[0055] In addition, since the PVA side chains contain a large number of polar hydroxyl groups and have strong hydrophilicity, they have poor water resistance and are prone to swelling and dissolution in water. Therefore, in addition to increasing the degree of cross-linking, it is also necessary to introduce hydrophobic segments into the cross-linked PVA skeleton macromolecules to reduce the content of polar groups, that is, to reduce the polarity of the polymer so that water cannot enter, or enters less. In response to this demand, the present invention adopts a technical solution of introducing long carbon chain hydrophobic segments.
[0056] The free amino group and alkylsulfonyl chloride undergo Hinsberg reaction to introduce long carbon chain hydrophobic segments on PVA. The introduction of long carbon chain hydrophobic segments further reduces the polarity of PVA, making it easier for PVA to bind to the PTFE surface.
[0057] Through the ring-opening reaction between the epoxy group of propylene / vinyl glycidyl ether and the hydroxyl group of PVA, photosensitive groups are introduced into PVA. After chemical modification of PVA, PVA is given photosensitivity, and the photosensitive groups are cross-linked under ultraviolet conditions, which improves the stability of PVA. In this way, low-energy ultraviolet light is used as the radiation source, and the equipment is easy to obtain, the investment cost is low, and the operation is simple.
[0058] The technical solution of the present invention is further described below in conjunction with specific examples.
[0059] Example 1:
[0060] 1) Take 5 g of polyvinyl alcohol 1799 (alcoholysis degree 98% to 99%) and 95 ml of deionized water, heat and stir in a 95°C water bath to completely dissolve to obtain a 5% solution;
[0061] 2) Add 2.0 g of p-aminobenzaldehyde and 1.0 g of glacial acetic acid to the dissolved 5% PVA solution and stir for 8 h to allow the aldehyde group to react with the hydroxyl group of PVA to undergo acetalization.
[0062] 3) After the reaction was completed, 1.1 g of dodecylsulfonyl chloride was added while stirring, and PVA-AbA was obtained after 3 hours.
[0063] 4) The PVA-AbA solution was transferred to a brown / light-opaque reaction vessel, and a certain amount of 100 mL of ethanol and 2.0 g of triethylamine were added. After heating to 100° C., 2.2 g of allyl glycidyl ether was added and stirred for 10 h to obtain the product PVA-AbA-Alsc-1.
[0064] 5) Clean the 0.4 micron PTFE microporous membrane with ethanol and dry it with hot air. Add 200 ml of methanol to a light-proof reaction vessel, and add the synthesized PVA-AbA-Alsc-1 and cationic photoinitiator. Place the cleaned PTFE microporous membrane in a reaction vessel, degas for 30-60 minutes with the help of ultrasound and vacuum-assisted systems, and then let it stand for 1-6 hours so that a layer of material containing polar groups is evenly coated on the PTFE. Take out the PTFE microporous membrane coated with PVA-AbA-Alsc from the reaction vessel, and after ultraviolet crosslinking for a period of time under ultraviolet light irradiation, a hydrophilic polytetrafluoroethylene microporous membrane is obtained.
[0065] Example 2:
[0066] 1) Take 5 g of polyvinyl alcohol 1799 (alcoholysis degree 98% to 99%) and 95 ml of deionized water, heat and stir in a 95°C water bath to completely dissolve to obtain a 5% solution;
[0067] 2) Add 1.0 g of p-aminobenzaldehyde and 1.0 g of glacial acetic acid to the dissolved 5% PVA solution and stir for 8 h to allow the aldehyde group to react with the hydroxyl group of PVA to undergo acetalization.
[0068] 3) After the reaction was completed, 0.7 g of dodecylsulfonyl chloride was added while stirring, and PVA-AbA was obtained after reacting for 3 h.
[0069] 4) The PVA-AbA solution was transferred to a brown / light-proof reaction vessel, and a certain amount of 100 ml of ethanol and 2.2 g of triethylamine were added. After heating to 100° C., 4.0 g of allyl glycidyl ether was added and stirred for 10 h to obtain the product PVA-AbA-Alsc-2.
[0070] 5) Clean the 0.4 micron PTFE microporous membrane with ethanol and dry it with hot air. Add 200 ml of methanol to a light-proof reaction vessel, and add the synthesized PVA-AbA-Alsc and cationic photoinitiator. Place the cleaned PTFE microporous membrane in a reaction vessel, degas with the help of ultrasound and vacuum-assisted systems for 30-60 minutes, and then let it stand for 1-6 hours so that a layer of material containing polar groups is evenly coated on the PTFE. Take out the PTFE microporous membrane coated with PVA-AbA-Alsc from the reaction vessel, and after ultraviolet crosslinking for a period of time under ultraviolet light irradiation, a hydrophilic polytetrafluoroethylene microporous membrane is obtained. Example 3:
[0071] 1) Take 10 g of polyvinyl alcohol 1799 (alcoholysis degree 98% to 99%) and 90 ml of deionized water, heat and stir in a 95°C water bath to completely dissolve to obtain a 10% solution;
[0072] 2) Add 4.0 g of p-aminobenzaldehyde and 1.5 g of glacial acetic acid to the dissolved 5% PVA solution and stir for 8 h to allow the aldehyde group to react with the hydroxyl group of PVA to undergo acetalization.
[0073] 3) After the reaction was completed, 3.0 g of dodecylsulfonyl chloride was added while stirring, and PVA-AbA was obtained after 3 hours.
[0074] 4) The PVA-AbA solution was transferred to a brown / light-proof reaction vessel, and a certain amount of 100 ml of ethanol and 2.2 g of triethylamine were added. After heating to 100° C., 4.0 g of allyl glycidyl ether was added and stirred for 10 h to obtain the product PVA-AbA-Alsc-3.
[0075] 5) Clean the 0.4 micron PTFE microporous membrane with ethanol and dry it with hot air. Add 200ML methanol to a light-proof reaction vessel, and add the synthesized PVA-AbA-Alsc and cationic photoinitiator. Place the cleaned PTFE microporous membrane in a reaction vessel, degas with the help of ultrasound and vacuum-assisted system for 30-60 minutes, and then let it stand for 1-6 hours so that a layer of material containing polar groups is evenly coated on the PTFE. Take out the PTFE microporous membrane coated with PVA-AbA-Alsc from the reaction vessel, and after ultraviolet crosslinking for a period of time under ultraviolet light irradiation, a hydrophilic polytetrafluoroethylene microporous membrane is obtained. Example 1-3, hydrophilic test result table of PVA-AbA-Alsc modified PTFE:
[0076]
[0077]
[0078] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that the present invention includes but is not limited to the contents described in the above specific embodiments. Any modification that does not deviate from the functional and structural principles of the present invention will be included in the scope of the claims.
Claims
1. A material for hydrophilic modification of polytetrafluoroethylene microporous membrane, characterized in that: The method comprises a PVA solution, aminobenzaldehyde, glacial acetic acid, alkylsulfonyl chloride and epoxy material, wherein the glacial acetic acid causes the aldehyde group in the aminobenzaldehyde to react with the hydroxyl group of the PVA to generate an acetal reaction and introduce an amino group, and the alkylsulfonyl chloride is used to introduce a hydrophobic chain segment into the PVA.
2. A material for hydrophilic modification of polytetrafluoroethylene microporous membrane according to claim 1, characterized in that: The PVA solution is prepared by stirring and dissolving polyvinyl alcohol and deionized water in a heated water bath.
3. A material for hydrophilic modification of polytetrafluoroethylene microporous membrane according to claim 2, characterized in that: The concentration of the PVA solution is 5%; and / or the temperature of the heating water bath is 95°C.
4. The material for hydrophilic modification of polytetrafluoroethylene microporous membrane according to claim 1, characterized in that: The aminobenzaldehyde is one or more of p-aminobenzaldehyde, o-phenylaminobenzaldehyde, m-phenylaminobenzaldehyde, p-acetylaminobenzaldehyde, 2,4-diaminobenzaldehyde and 2-amino-3,5-dibromobenzaldehyde.
5. The material for hydrophilic modification of polytetrafluoroethylene microporous membrane according to claim 4, characterized in that: The added amount of aminobenzaldehyde accounts for 5-15% of the mass percentage of the PVA solution; and / or the added amount of glacial acetic acid accounts for 1-5% of the mass percentage of the PVA solution.
6. The material for hydrophilic modification of polytetrafluoroethylene microporous membrane according to claim 1, characterized in that: The alkylsulfonyl chloride is one or more of pentanesulfonyl chloride, octanesulfonyl chloride, undecanesulfonyl chloride, dodecanesulfonyl chloride, pentadecanesulfonyl chloride, heptadecanylsulfonyl chloride and octadecanesulfonyl chloride.
7. The material for hydrophilic modification of polytetrafluoroethylene microporous membrane according to claim 6, characterized in that: The mass percentage of the added alkylsulfonyl chloride to the PVA solution is 2-15%.
8. The material for hydrophilic modification of polytetrafluoroethylene microporous membrane according to claim 1, characterized in that: The epoxy material is one or more of 4-vinylbenzyl glycidyl ether, allyl glycidyl ether and glycidyl methacrylate.
9. A method for preparing a hydrophilic modified material, characterized in that: The method for preparing the material according to any one of claims 1 to 8 comprises the following steps: Adding aminobenzaldehyde to the PVA solution; Add glacial acetic acid and stir to allow the aldehyde group in aminobenzaldehyde to react with the hydroxyl group of PVA to form an acetal and introduce an amino group; After the acetalization reaction is completed, alkylsulfonyl chloride is added and stirred to introduce hydrophobic segments into PVA to obtain a PVA-AbA solution; The PVA-AbA solution is transferred to a light-proof reaction container, and an alcohol solvent is first added to prepare a 1-5% solution, and triethylamine is added at a mass percentage of 0.5-3% of the solution for catalysis. Then, the epoxy material is added and stirred after heating to a set temperature and stirring for a set time to react to obtain the product PVA-AbA-Alsc material.
10. The method for preparing a hydrophilic modified material according to claim 9, characterized in that: After catalysis, the mixture is heated to 100° C. and stirred for 4-6 hours; and / or, after adding the epoxy material, the stirring time is 10-12 hours.
